Violência interpessoal: estudo descritivo dos casos não fatais atendidos em uma unidade de urgência e emergência referência de sete municípios do estado de São Paulo, Brasil, 2008 a 2010 - Cecílio, Lenise Patrocínio Pires [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Rovida, Tânia Adas Saliba [UNESP]; Queiroz, Ana Paula Dossi de Guimarães e [UNESP]; Garbin, Artênio José Isper [UNESP] (FapUNIFESP (SciELO), 2012)
Objective: to describe the profile of non-fatal cases related to interpersonal violence treated in an emergency care unit of reference that serves seven municipalities of the state of São Paulo, Brazil, from 2008 to 2010. Methods: the study data came from the cases reported from the Epidemiological Vigilance in Penápolis-SP to the Brazilian Information System for Notifiable Diseases; variables were shown according to the Notification/Investigation Individual Formulary of Domestic, Sexual, and/or other Types of Violences. Results: 109 occurrences were studied; most of the victims were young and female (93.6%); and the aggressors, mostly were men (57.8%), partners or relatives/acquaintances of victims. Physical violence was the main form of aggression (93.6%), principally in the home (67.9%), on Sunday (16.5%), between 6:01pm and 12:00pm (57.8%). Conclusion: the cases reported had a consistent profile of domestic family violence against women, different from other studies about interpersonal violence in large cities and metropolitan regions

Objetivo: descrever o perfil dos casos não fatais de violência interpessoal atendidos em uma unidade de urgência e emergência de referência para sete municípios do estado de São Paulo, no período 2008- 2010. Métodos: os dados dos casos notificados à Vigilância Epidemiológica de Penápolis foram obtidos do Sistema de Informação de Agravos de Notificação (Sinan); as variáveis foram apresentadas conforme a Ficha de Notificação/Investigação Individual de Violência Doméstica, Sexual e/ou Outras Violências. Resultados: foram estudados 109 casos; a maior parte das vítimas eram jovens do sexo feminino (93,6%) e os agressores, majoritariamente homens (57,8%), cônjuges ou parentes/conhecidos das vítimas. A violência física foi a principal forma de agressão (93,6%), ocorrida, principalmente, nas residências (67,9%), aos domingos (16,5%), entre 18:01 e 24:00 horas (57,8%). Conclusão: os casos notificados apresentaram perfil compatível com violência intrafamiliar doméstica contra mulheres, diferentemente dos estudos sobre violência interpessoal nas grandes cidades e Regiões Metropolitanas
Interpersonal violence: descriptive study of not fatal cases assisted in an emergency reference unity to seven municipalities of the state of São Paulo, Brazil, from 2008 to 2010
Keywords: Violence; Emergency medical services; Aggression; Epidemiology; Descriptive; Public health; Violência; Serviços médicos de emergência; Agressão; Epidemiologia descritiva; Saúde pública